Behavioural responses of Irrawaddy dolphins (Orcaella brevirostris) to a dead conspecific - Jones, Amy L; Tubbs, Sarah E; Croxford, Eve M (eScholarship, University of California, 2021)
Cetacean behaviour has long attracted scientific attention as humans endeavour to discover what makes these mammals so emotive and engaging. To date, much of this research has focussed on abundant and widely distributed cetacean species such as bottlenose dolphins ( Tursiops truncatus ) and humpback whales ( Megaptera novaeangliae ). As an endangered and often evasive species, research regarding Irrawaddy dolphin ( Orcaella brevirostris ) behaviour is limited. This study uses data collected by The Cambodian Marine Mammal Conservation Project, to investigate the behavioural responses of Irrawaddy dolphins towards a dead conspecific. During a routine boat survey of Cambodia’s Kep Archipelago, the carcass of an adult female Irrawaddy dolphin was recovered and attached to the stern of the research vessel and promptly towed to the research island for further examination. During this survey, there was a four-fold increase in the number of Irrawaddy dolphin groups observed compared to the seasonal average (post-monsoon), in addition to an atypically positive response towards the research vessel and an atypical increase in the number of behavioural events observed. These behavioural variations were believed to be in response to the towed dead conspecific. The authors propose future dedicated research to assess the complexity of wild Irrawaddy dolphin behaviour, cognition, and awareness, to robustly exemplify the species’ apparent sentience and intelligence.